Effects of laser beam energy on the pulsed Nd:YAG laser welding of thin sheet corrosion resistant materials - Ventrella, Vicente Afonso [UNESP]; Berretta, Jose Roberto; Rossi, Wagner de; Tieu, A. K.; Zhu, H.; Zhu, Q. (Trans Tech Publications Ltd, 2014)
The aim of this study was to value the possibility to join, for pulsed Nd:YAG laser welding, thin foils lap joints for sealing components in corrosive environment. Experimental investigations were carried out using a pulsed neodymium: yttrium aluminum garnet laser weld to examine the influence of the pulse energy in the characteristics of the weld fillet. The pulse energy was varied from 1.0 to 2.5 J at increments of 0.25 J with a 4 ms pulse duration. The base materials used for this study were AISI 316L stainless steel and Ni-based alloys foils with 100 mu m thickness. The welds were analyzed by electronic and optical microscopy, tensile shear tests and micro hardness. The results indicate that pulse energy control is of considerable importance to thin foil weld quality because it can generate good mechanical properties and reduce discontinuities in weld joints. The ultimate tensile strength of the welded joints increased at first and then decreased as the pulse energy increased. In all the specimens, fracture occurred in the top foil heat-affected zone next to the fusion line. The microhardness was almost uniform across the parent metal, HAZ and weld metal. A slight increase in the fusion zone and heat-affected zone compared to those measured in the base metal was observed. This is related to the microstructural refinement in the fusion zone, induced by rapid cooling of the laser welding. The process appeared to be very sensitive to the gap between couples.
Keywords: Laser welding; Nd:YAG laser; AISI 316L; Ni-alloys; Thin foils